EFFECT OF ENZYME SUPPLEMENTATION ON THE PERFORMANCE OF BROILER CHICKENS - BADSHAH, F; LATIF, A; MAQBOOL, M; AHMAD, M; ZAFAR, MB; ALI, MA; FAIZ, S; SARWAR, MI; ADNAN, M; SOHAIL, M (Biological and Clinical Sciences Research Journal, 2023)
To evaluate the influence of xylanase, phytase, and their combination on broiler growth, nutrient digestibility, bone mineralization, and gut morphology. A randomized complete block design was employed for this study. 400 day-old broiler chicks (Ross 308) were dispensed to four treatment bunches with five reproduces per treatment. The birds were haphazardly disseminated among the medicines in light of starting body weight to guarantee homogeneity across gatherings. Broilers supplemented with xylanase and combining xylanase and phytase showed numerically higher average body weights compared to the control and phytase-only groups. However, statistical significance was observed only in the xylanase and combination groups (p < 0.05). The combination of xylanase and phytase demonstrated the lowest FCR, indicating improved feed efficiency compared to other groups (p < 0.05). Xylanase supplementation also resulted in significantly lower FCR than the control (p < 0.05). It is concluded that enzyme supplementation, specifically the combination of xylanase and phytase, significantly enhanced broiler growth, nutrient utilization, and bone health.